EFFECTS OF ADVERTISING COLORS ON SOCIETY: विज्ञापन के रंगों का समाज पर प्रभाव - Gupta, Dimple (International Journal of Research -GRANTHAALAYAH, 2014)
It is visible to us only because of the color of the objects in the ground. Objects of the same color are seen differently due to less and more amount of light on the ground. We get this diverse color from the sun itself. There are seven types of colors in the rays of the sun. And it is through them that the rainbow is formed in the sky. Color is a powerful psychological tool. Each color leaves different effects. Colors have a great impact on society, if color is removed from human life and nature, then all the people on this earth will start to look like monotonous, every person has different feelings towards colors. वस्तुओं के धरातल में रंग होने के कारण ही वह हमें दिखाई देती है। धरातलों पर प्रकाश की मात्रा कम व अधिक होने से एक ही रंग की वस्तुएँ अलग-अलग दिखाई देती है। यह विविध रंग हमें सूर्य के द्वारा ही सब वस्तुओं को प्राप्त होता है। सूर्य की किरणों में सात प्रकार के रंग होते है। और उन्हीं के द्वारा ही आकश में इन्द्रधनुष बनता है। रंग एक शक्तिशाली मनोवैज्ञानिक औजार है। हर रंग अलग-अलग प्रभाव छोड़ता है। रंगों का समाज पर बहुत प्रभाव पड़ता है यदि मानवीय जीवन और प्रकृति से रंग निकाल दिया जाय तो इस धरती पर सब सूना-सूना नीरस सा लगने लगेगा रंगों के प्रति हर व्यक्ति की भावनाएँ अलग-अलग होती है।